Mice with a naturally occurring DISC1 mutation display a broad spectrum of behaviors associated to psychiatric disorders - Gómez-Sintes, Raquel; Kvajo, Mirna; Gogos, Joseph A.; Lucas, José J. (Frontiers in Behavioral Neuroscience, 2014)
DISC1 (disrupted in schizophrenia-1) gene is associated with several neuropsychiatric disorders as it is disrupted by a balanced translocation involving chromosomes 1 and 11 in a large Scottish pedigree with high prevalence of schizophrenia, bipolar disorder and major depression. Since its identification, several mouse models with DISC1 genetic modifications have been generated using different approaches. Interestingly, a natural deletion of 25bp in the 129 mouse alters the DISC1 gene reading frame leading to a premature stop codon very close to the gene breakpoint in the mutant allele of the Scottish family. In the present study we confirmed that the 129DISC1Del mutation results in reduced level of full length DISC1 in hippocampus of heterozygous mice and we have characterized the behavioral consequences of heterozygous 129DISC1Del mutation in a mixed B6129 genetic background. We found alterations in spontaneous locomotor activity (hyperactivity in males and hypoactivity in females), deficits in pre-pulse inhibition and also increased despair behavior in heterozygous 129DISC1Del mice, thus reproducing typical behaviors associated to psychiatric disorders. Since this mouse strain is widely and commercially available, we propose it as an amenable tool to study DISC1-related biochemical alterations and psychiatric behaviors.